Lalit Mohan Sharma. Imaginary Knots: Poems, Authors Press, New Delhi. 2024 (Literary Voice, 2024)
Life is not a series of gig lamps symmetrically arranged; life is a luminous halo, a semi-transparent envelope surrounding us from the beginning of consciousness to the end, says Virginia Woolf. And the poet’s vocation is to charter this irregular flow of life, and try to inject meaning into the anarchic, and if possible, order the chaos.In the ordered universe, only man is an aberration. He is in fact an organized chaos, working hard to rework his own pattern and trying to find meaning in jumbled existence. Catch a thread in a jumble and you can unknot it by and by.  But human mind is a jumble which knows no easy solutions.  The unrest, angst, the stir that marks human mind at this juncture of existential history of mankind is what makes the warp and woof of Dr Lalit 's poetry. If poetry is an image of our lives, his poems go a step forward and present not only the outward image, but also lay bare the inside corrosion suffered by the human soul. The most corrosive of all elements is the passion for greed, more and more, and a complete lack of sensitivity towards others who might suffer when we blow our trumpet.
Keywords: Poetry; Imagination; Humanity; passion